Quality Attributes and In Vitro Bioequivalence of Different Brands of Amoxicillin Trihydrate Tablets - Moawia M. Al-Tabakha; Khairi M. S. Fahelelbom; Dana Emad Eddin Obaid; Sadik Sayed (Pharmaceutics, 2017)
Bacterial resistance and antibiotic drug effectiveness can be related to administering generic products with a subtherapeutic dose or poor in vivo drug release. The aim of this study was to investigate whether locally marketed amoxicillin tablets have the required chemical and physical attributes, including in vitro bioequivalence performance. Five generic products (T1, T2, T3, T4, and T5) containing combination of amoxicillin trihydrate and potassium clavulanate as 1 g strength present in immediate release tablets were compared to the reference listed drug product Augmentin® (R) for weight variation, friability, resistance to crushing, and chemical content of amoxicillin. Difference (ƒ1) and similarity (ƒ2) factors were calculated to assess in vitro bioequivalence requirements. The tablets from different products have shown compliance with the pharmacopeial requirements of the performed tests. The measured resistance to crushing of tablets did not influence the dissolution time. Three generic products released more than 85% of amoxicillin by the first 15 min as did the reference product and were considered as bioequivalent products. T1 and T4 had ƒ1 values of 16.5% and 25.4% respectively and their ƒ2 values were 44.5 and 34.6 respectively, indicating failure to meet in vitro bioequivalence requirements. Tablet formulations can play an important role in achieving bioequivalence. Independent investigations such as this study serve as an important tool to reveal possible inferior or noncompliant products that may find their way to the market.